Association between plasma ADAMTS-7 levels and severity of disease in patients with stable obstructive coronary artery disease. Issue 48 (November 2016) - Yu, Jie; Zhou, Boda; Yu, Haiyi; Han, Jiangli; Cui, Ming; Zhang, Fuchun; Wang, Guisong; Guo, Lijun; Gao, Wei
Abstract : Abstract: The metalloproteinase family of a disintegrin and metalloproteinase with thrombospondin motifs-7 (ADAMTS-7) was reported to be a novel locus associated with human coronary artery disease. This study aimed to investigate plasma ADAMTS-7 levels in stable obstructive CAD patients and elucidate the relationship between plasma ADAMTS-7 levels and the severity of CAD assessed by the Syntax score. This was a single center cross-sectional study performed in 182 CAD patients. ELISA was used to measure plasma ADAMTS-7 levels. All patients were divided into subgroup according to the ADAMTS-7 median in this cohort: high group with ADAMTS-7 ≥0.99 ng/mL and low group with ADAMTS-7 <0.99 ng/mL. Furthermore, all patients were divided into tertiles according to their Syntax scores (low group: Syntax score ≤10.0; moderate group: 10.0 <Syntax score ≤18.0; high group: Syntax score >18.0). We followed up the participants continuously until the first major adverse cardiovascular event (MACE) for a mean time of 22.0 months. Plasma ADAMTS-7 levels in the high Syntax score group were significantly higher compared with the low Syntax score group (3.29 [0.08–26.3] ng/mL vs 1.24 [0.15–8.78] ng/mL, P  = 0.010). Plasma ADAMTS-7 levels were significantly positively correlated with the Syntax score tertiles ( r  = 0.157, P  = 0.035). Logistic regression analysis indicated that the plasma ADAMTS-7 level was one of the independent predictors for the Syntax score tertiles ( B  = 1.118, 95% CI: 1.194–7.830, P  = 0.020), together with HbA1c ( B  = 0.946, 95% CI: 1.248–5.312, P  = 0.010), uric acid ( B  = –0.019, 95% CI: 0.974–0.988, P <0.001), and coronary artery calcium score ( B  = –0.001, 95% CI: 0.998–0.999, P  < 0.001). Compared with the low ADAMTS-7 group, the high ADAMTS-7 group had significantly higher Syntax score (17.10±8.42 vs 14.96 ± 8.11, P  = 0.047). Kaplan–Meier analysis showed patients in the high plasma ADAMTS-7 group tend to have a lower event-free survival rate than patients in the low plasma ADAMTS-7 group, unfortunately, no difference was detected (86.8% vs 88.0%, log rank = 0.314, P  = 0.575). The plasma ADAMTS-7 level was positively correlated with the Syntax score significantly. The elevated plasma ADAMTS-7 level may be involved in the severity of disease in patients with stable coronary artery disease.